1983
DOI: 10.1002/ajmg.1320150316
|View full text |Cite
|
Sign up to set email alerts
|

A newly recognized neuroectodermal syndrome of familial alopecia, anosmia, deafness, and hypogonadism

Abstract: We describe a large, three generation kindred in which 16 individuals were affected with alopecia, hyposmia or anosmia, conductive deafness associated with protruding ears, microtia, and/or atresia of the external auditory canal, hypogonadotropic hypogonadism due to LH/FSH deficiency, and a greater than normal tendency to dental caries. Variable manifestations include mild facial asymmetry, mental retardation, congenital heart defect, and cleft palate. This seems to be a previously undescribed pleiotropic auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
1
2

Year Published

1985
1985
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 6 publications
7
37
1
2
Order By: Relevance
“…The case described here shares many important features with the family described by Johnson et al [1983]. The patient's most significant findings of microtia and ectodermal dysplasia including hypotrichosis are similar to those described in their family, and our patient's physical appearance is strikingly similar to that seen in their case 111-10.…”
Section: Discussionsupporting
confidence: 79%
“…The case described here shares many important features with the family described by Johnson et al [1983]. The patient's most significant findings of microtia and ectodermal dysplasia including hypotrichosis are similar to those described in their family, and our patient's physical appearance is strikingly similar to that seen in their case 111-10.…”
Section: Discussionsupporting
confidence: 79%
“…However, these features were absent in our patients. Johnson et al [1983] described hypogonadism and alopecia in association with anosmia, conductive deafness, congenital heart defect, cleft palate, and mental retardation, and suggested a new autosomal dominant neuroectodermal syndrome (OMIM-147770) [Johnson et al, 1983]. The autosomal dominant trait and some clinical findings such as anosmia, congenital heart defect, and cleft palate rule out the patients reported here.…”
Section: Discussioncontrasting
confidence: 60%
“…The association of hypogonadism and alopecia is rare and has only been reported occasionally [Crandall et al, 1973;Johnson et al, 1983;Johnston et al, 1987;Devriendt et al, 1996a,b]. In 1985, Al-Awadi et al [1985] reported three sibs with partial alopecia, hypogonadism and defective Mullerian development in the two sisters.…”
Section: Introductionmentioning
confidence: 94%
“…It induces embryologic anomalies of the ectoderm and neuroectoderm of the first and second brachial arches, Rathke's pouch, and the diencephalon. 36,37 Overlaps between Johnson-McMillin and CHARGE syndrome exist because CHARGE syndrome also induces anomalies of neuroectoderm development and neural crest migration. Overlaps between CHARGE and Kallmann syndromes are interesting for several reasons.…”
Section: Discussionmentioning
confidence: 99%